Monitoramento participativo e accountability governamental: o estudo de caso do “Cuidando de Meu Bairro” - Ivan Trizi Amorim; Gisele Craveiro; Jorge Machado (Confins)
This paper aims to verify the influence of independent platforms on the Government Accountability. With this purpose, we discuss the concept and application of accountability to analyse the tool named "Caring for My Neighborhood" (CMB), which is a social platform for monitoring and controlling town´s public spending. Bibliometric research, literature review and uses analysis of the platform were carried out. It was verified that, despite the initial steps and the great difficulties that still remain, the platform has been contributing to the promotion of governmental accountability, being necessary to train and consolidate communities of developers and users for such purpose.